Contribution of Higher-Order Nonlinearity on Dust Acoustic Solitary Waves in Complex Plasma with a High-Energy Tail Ion Distribution - Younsi, Smain; Benzekka, Moufida; Amour, Nabil Arab and Rabia (Journal of Applied Nonlinear Dynamics, 2026)
The problem of dust acoustic dressed solitons is addressed in an unmagnetized collisionless dusty plasma with ions satisfying a $κ$-distribution. The approach based on the expanding of the Sagdeev potential up to the fourth-order has been generalized to the non-Maxwellian dusty plasma. This approach yields a second order inhomogeneous differential equation termed dressed soliton. The resulting dressed soliton is then expressed as a sum of the usual K-dV solution and the higher-order nonlinearity terms. The range of main parameters ($κ$ and $λ$) where the higher order correction is valid is explored. In particular, the suprathermal parameter values required to the valid dressed solitons are shifted toward higher values as the velocity $λ$ increases. Furthermore, our numerical investigations reveal that the main quantities of all localized structures are significantly modified by the suprathermal effects. Our results should help in providing a good fit between theoretical and experimental results.